Recommended Practices for More Accessible Quantification of Low‐Concentration Aqueous Phase Products in Photo/Electrocatalytic CO2/N2 Fixation - Li, Dong; Xu, Ning; Zhao, Yunxuan; Shi, Run; Zhou, Chao; Zhang, Li‐Ping; Zhang, Tierui (Advanced energy materials, 2024)
The sustainable development of novel photo/electrocatalytic CO2/N2 fixation for chemical synthesis is predicated on reliable, accurate, and rapid detection methods. The directness, specificity, and simultaneity in detecting multiple molecules of the 1H nuclear magnetic resonance (1H‐NMR) technique have aroused increasing interest in photo/electrocatalysis. Thus far, two data processing means have been developed for the precise 1H‐NMR data processing: peak integral and peak height methods. However, few detailed studies offer a clear steer for choosing data processing methods for the concerned products in photo/electrocatalysis, especially the guidelines under the conditions of baseline distortions induced by water suppression. Herein, the feasible practices are restudied to quantify classical products in photo/electrocatalytic CO2/N2 fixation. On the basis of experimental results, 1H‐NMR data processing methods (peak integral and peak height methods) are found to convey different applicability for the different low‐concentration products, while introducing water suppression in the 1H‐NMR tests. The essential reason can be attributed to the baseline distortions caused by the water suppression, which arouses differentiated deviation of peaks with different peak widths. With this in mind, an accessible quantification criterion is provided to avoid superfluous input of time or cost in precise 1H‐NMR detection of low‐concentration products. Recommended practices based on the established criterion or framework are proposed for the more accessible quantification of low‐concentration aqueous phase products. It is further expected to alert to the significance of 1H‐NMR method selection and light up the precise product detection via 1H‐NMR in the case of introducing water suppression.